Alpha-fetoprotein level in fetuses, infants, and children with ovarian masses: a literature review - Matonóg, Aleksandra; Drosdzol-Cop, Agnieszka (Frontiers in Endocrinology, 2024)
Alpha-fetoprotein (AFP) is a serum protein highly produced during the fetal period. It is also known as a biomarker of various pathologies. Commonly, tumors requiring diagnosis and monitoring through AFP determination appear during the first year of life, with poorer outcomes when presenting in fetal life. Due to advancements in imaging technology, the detectability of ovarian masses in infants is higher. However, the use of AFP as a biomarker could improve diagnosis in cases when imaging and histological examinations are not sensitive enough to detect tumors. From the outcome of our investigation, it is possible to conclude that there is evidence of an association between increased AFP levels and ovarian masses. However, previous studies have presented contradictory and unverified results, with the authors emphasizing that future research is needed. In this article, an analysis of the available literature on AFP as a biomarker of ovarian masses in children was performed. Two types of literature were reviewed: guidance and published studies (clinical trials, reviews, and systematic reviews). We searched the Embase, PubMed, ScienceDirect, and Web of Science databases to collect essential data.